The Influence of Brand Awareness and Electronic Word of Mouth on Purchase Decisions with TikTok Social Media Marketing Live Stream as mediation: A Study on Brand Cosmetic Product Consumers; Skintific in Indonesia - Mira Puspita; Ratlan Pardede (Jurnal Indonesia Sosial Sains, 2023)
Currently, live-streaming shopping on social media is growing rapidly. This is because the development of cellular communication technology is also increasingly developing. This research aims to investigate how Brand Awareness and E-WOM influence consumer decisions mediated by live streaming on social media for a cosmetics brand. The population of this research is TikTok customers who use the application to purchase their product needs. Data collection uses an online survey with Google Forms. There were 403 respondents who met the respondent criteria. The analytical method used is SEM PLS. The research results show that Brand Awareness has a positive and significant effect on Purchase Decision, E-WOM has a positive and significant effect on Purchase Decision, Brand Awareness has a positive and significant effect on Live Streaming, E-WOM has no direct effect on Live Streaming, Live Streaming has a positive effect and significant to Purchase Decision, Live Streaming mediates Brand Awareness to Purchase Decision, and Live Streaming does not mediate E-WOM to Purchase Decision